Autophagy in the immune response to tuberculosis: clinical perspectives - KEANE, JOSEPH; HARRIS, JAMES; LAVELLE, EDWARD; NI CHEALLAIGH, CLIONA; Hope, J.C. (My University, 2011)
A growing body of evidence points to autophagy as an essential component in the immune response to tuberculosis. Autophagy is a direct mechanism of killing intracellular Mycobacterium tuberculosis and also acts as a modulator of proinflammatory cytokine secretion. In addition, autophagy plays a key role in antigen processing and presentation. Autophagy is modulated by cytokines; it is stimulated by T helper type 1 (Th1) cytokines such as tumour necrosis factor (TNF)‐α and interferon (IFN)‐γ, and is inhibited by the Th2 cytokines interleukin (IL)‐4 and IL‐13 and the anti‐inflammatory cytokine IL‐10. Vitamin D, via cathelicidin, can also induce autophagy, as can Toll‐like receptor (TLR)‐mediated signals. Autophagy‐promoting agents, administered either locally to the lungs or systemically, could have a clinical application as adjunctive treatment of drug‐resistant and drug‐sensitive tuberculosis. Moreover, vaccines which effectively induce autophagy could be more successful in preventing acquisition or reactivation of latent tuberculosis.
PUBLISHED
Keywords: Autophagy; Inflammasome; Rapamycin; TNF-a; Vaccination; Vitamin D; Immunology, Inflammation & Infection